Close Binary Stars Modeled by Two Prolate Ellipsoids in Synchronous Rotation - Antonio Elipe; M. Lívia da Costa; Luca Piccotti; Eva Tresaco (The Astronomical Journal, 2023)
The presence of tidal deformations in close binary stars has already been confirmed by astronomical observations. The present paper aims to simply address an astronomy problem, studying the relative movement of close binaries disturbed by their mutual deformation through some basic concepts and tools of celestial mechanics. For this purpose, the tidal effect is modeled by considering that each star is an elongated revolution ellipsoid in such a way that axes of revolution are coincident, and their largest axes point toward each other along the motion. The potential for mutual attraction is then obtained, resulting in a perturbed Keplerian system with perturbation proportional to the inverse of the cubic distance between the stars, thus being a one-degree-of-freedom problem and, therefore, integrable. The effective potential, the integrals of energy and angular momentum, and the Laplace vector are used to obtain qualitative information about the dynamics before integrating it. The motion describes a rosette-like orbit with periodic osculating elements, or a circle when the energy is a local minimum. Finally, an analytical solution is presented in terms of elliptic functions by using a regularizing and linearizing function.